Orbito-frontal cortex and thalamus volumes in obsessive-compulsive disorder before and after pharmacotherapy - Atmaca, Murad; Mermi, Osman; Yildirim, Hanefi; Gurok, M. Gurkan (Springer, 2016)
In the present study, we focused on the key brain regions, OFC and thalamus, to investigate the roles of antiobsessional agents on volume changes of these brain regions after 12 weeks of anti-obsessional treatment in patients with obsessive-compulsive disorder (OCD). Fourteen patients with OCD and the same number of healthy controls were included in the study. At baseline, the volumes of the OFC and thalamus were compared by using magnetic resonance imaging (MRI) between groups. The volumes of OFC and thalamus were evaluated before and after the anti-obsessional drug treatment solely in the patient group. Our study revealed that thalamus volumes were reduced statistically significantly throughout the treatment period. However, we found that OFC volumes did not change statistically significantly throughout the treatment period. In summary, our study found that anti-obsessional drug treatment had an effect on thalamus volumes throughout the treatment period for both sides but not on OFC volumes. However, future studies with larger sample are required.
Keywords: Pharmacotherapy; OCD; Thalamus; OFC